Comparison of electron–phonon and hole–phonon energy loss rates in silicon. (January 2015) - Richardson-Bullock, J.S.; Prest, M.J.; Shah, V.A.; Gunnarsson, D.; Prunnila, M.; Dobbie, A.; Myronov, M.; Morris, R.J.H.; Whall, T.E.; Parker, E.H.C.; Leadley, D.R.
Highlights: We investigate carrier-phonon coupling in p and n doped silicon. We utilise tunnel junction thermometry to measure carrier temperature. Holes are more strongly coupled to the lattice temperature than the electrons. Comparisons are made to theoretical predictions. Abstract: The hole-phonon energy loss rate in silicon is measured at phonon temperatures ranging from 300 mK to 700 mK. We demonstrate that it is approximately an order of magnitude higher than the corresponding electron–phonon energy loss rate over an identical temperature range.